Bad Man's Range [large type] - Cole, Jackson (Wheeler Publishing, A part of Gale, Cengage Learning, 2013)
The man named Ellsworth was caught trespassing and discovered too late that Colonel Madison Crile, owner of Mace Ranch, meant business. He had trespassed his way into hell. And just when he thought he didn't have a prayer, Ranger Jim Hatfield appeared on the scene, Colts flaming.